BAHAN ALAM (NATURAL PRODUCTS) SEBAGAI AGEN KEMOPREVENTIV DAN KEMOTERAPI KANKER - Asih Triastuti (Universitas Islam Indonesia, 2004)
ABSTRACTMedicinal plant has formed the basis of sophisticated traditional medicine systems that havebeen existed for thousands of years. Many advances in the chemistry of novel bioactive naturalproducts are reported. This article looks at potential chemotherapeutic and chemopreventive ofsome natural products such as curcumin, polyphenol, and dietary phytochemicals. Apparently, themedicinal plants will be continue to be important source of lead compounds for the new drugdiscovery and development in the future especially for the new anti cancer drug.Key word: bahan alam, kemopreventiv, kemoterapi, kanker